Emotional Intelligence in the Educational and Therapeutic Community in Nepal - Rybak, Christopher; Maharjan, Chhori Laxmi; Adhikari, Anubha (Journal of Education and Research, 2010)
Emotional intelligence has been gaining increased attention in both the educational as well as therapeutic communities of Nepal. Research suggests that development of emotional intelligence has a significant influence on an individual’s achievements including academic success and is seen as a key aspect of positive development (Mayer, Salovey, & Caruso, 2004). Ankur Counseling Center in Kathmandu was established in 2006, primarily to work with children who have experienced great stress in their lives. Counselors at Ankur have been using play and sand tray therapy to understand the emotional lives of their clients, as well as to assist the process of emotional healing. DOI: http://dx.doi.org/10.3126/jer.v2i0.7621 Journal of Education and Research Vol. 2, 2010 p.35-43